The Effect of Methyl Eugenol Block Plus on Bactrocera dorsalis Complex Total Captured in Chili Plantation - Agus Susanto; Wahyu Daradjat Natawigena; Luciana Djaya; Tohidin Tohidin; Fauza Saputra (Jurnal Biodjati, 2021)
Fruit flies (Bactrocera spp.) are an important pest for horticultural crops, especially fruits and vegetables. One of the most effective and eco-friendly methods to control male and female fruit flies is by usingtraps that use Methyl Eugenol (ME) block plus fruit essence as an attractant. The purposes of this research were to acquire the most effective formulation of ME Block plus fruit essence to catch the most male and female fruit flies on the chili plantation and to detremine the increase in total of fruit flies caught. This research started from December 2017 to January 2018 at Cibeureum Village, Sukamantri District, Ciamis Regency, West Java Province. The research was conducted using a randomized block design consisting of 8 treatments and 3 repetitions. The treatments consisted of adding fruit essence to the ME block: 2 ml of ME on cotton; 2 ml of ME block; 2 ml of ME block + 4 ml of mango essence; 2 ml of ME block + 4 ml of orange essence; 2 ml of ME block + 4 ml of guava essence; 2 ml of ME block + 4 ml of star fruit essence; 2 ml of ME block + 4 ml of chili essence; Antilat (Organic pesticide) as a comparison. The results showed that ME block plus fruit essence has increased the total of male fruit flies caught, but it did not attract female fruit flies. The best combinations with the highest average of male fruit flies caught were ME block plus orange essence with 750.67/5 week, followed by ME block plus chili essence with 746.00/5 week